Pelatihan Penerapan Pembelajaran Matematika Berbasis Etnomatematika untuk Meningkatkan Pemahaman Konsep Matematika dengan Kearifan Lokal: Training on the Application of Ethnomathematics-Based Mathematics Learning to Improve Understanding of Mathematical Concepts with Local Wisdom - Somakim Somakim; Indaryanti Indaryanti; Novika Sukmaningthias; Novita Sari; M. Hasbi Ramadhan; Yovika Sukma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The importance of ethnomathematics lies in its ability to integrate local cultural contexts into mathematics instruction, thereby facilitating a deeper and more relevant understanding of concepts for students. This research aims to train teachers to develop ethnomathematics-based mathematics learning that integrates local wisdom into the learning process. The approach used is participatory-collaborative, in which partners are not only beneficiaries but also actively participate in planning and implementing activities. The partners in this activity are junior high school mathematics teachers in Ilir Timur I District, Palembang City, who are under the auspices of the Palembang City MGMP. The results of this activity show that the ethnomathematics-based approach makes learning more interesting, easier to understand, and relevant to daily life. These results are also supported by the questionnaires distributed, which show that 92.33% are very satisfied with this activity. This activity is expected to be the initial step for teachers to continue developing contextual and local wisdom-based innovations in mathematics learning.